DEVELOPMENT OF SERVICE QUALITY FOR STUDY PROGRAMME ‘THERAPEUTIC MASSAGE’ - Veseta, Una; Svētiņa, Karīna; Onževs, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Higher education institutions try to provide best quality study and services in order to satisfied student. The purpose of this paper is to develop recommendations to improve service quality for study programme ‘Therapeutic massage’ (EQF study level 5). The standard questionnaire SERVQUAL (five dimensions - reliability, assurance, tangibles, empathy and responsiveness), emphasizing on measuring the gap between level of current and expected service quality was used. In total 122 students (94% of study programme`s students) have participated in research. The study examines the validity of SERVQUAL in assessing students` satisfaction with study programme. Reliability Coefficient Cronbach's Alpha 0.884. The research found that in the study programme there is a gap of current and expected service quality in dimensions empathy (gap mean score -0.28), tangibles (gap mean score -0.38), responsiveness (gap mean score -0.30) indicating that development need to be implemented to enhance the service quality. Based on the research results obtained, recommendations for improvement of service quality were developed.